ADVANCEMENTS IN DEVELOPMENT AND CLINICAL TRIALS OF ERYTHROCYTES AS DRUG DELIVERY SYSTEMS - Drvenica, Ivana; Ilić, Vesna (Archives of Pharmacy, 2023)
In recent years, cell-based delivery systems have emerged as an effective approach for treating "modern age" diseases due to their numerous advantages over natural or synthetic carriers. Thus, researchers and clinicians have focused on biological carriers derived from bacterial and mammalian cells (1). Erythrocytes, platelets, leukocytes, stem cells, fibroblasts, hepatocytes, and cancer cells are among the various types of cells that have been utilized as novel drug delivery systems. Among these, erythrocytes have been extensively studied and have shown great potential for controlled, prolonged, and targeted drug delivery, with real clinical applications on the horizon (2,3). The success of clinical trials involving autologous L-asparaginase and dexamethasone sodium phosphate loaded human erythrocytes over the past two decades (Phase 1 and 3, respectively) supports this notion (2). These procedures have yielded very satisfactory results in treating severe inflammatory/malignant diseases without associated side effects, from both the pharmacokinetic and pharmacodynamic perspectives. The lecture will offer a well-rounded summary of the ongoing efforts in developing drug delivery systems based on erythrocytes, highlighting the significant clinical progress achieved so far, along with safety, efficacy, and tolerability reports. The advantages and drawbacks are specifically summarized to get a critical point of view on existing and future medical applications of erythrocyte-based drug carriers. As an example of complexity in research toward development of such erythrocyte-based drug delivery systems starting from animal erythrocyte, morphological, biochemical and drug release profile assessment will be reviewed.